A failure analysis of invasive breast cancer: Most deaths from disease occur in women not regularly screened. Issue 18 (9th September 2013) - Webb, Matthew L.; Cady, Blake; Michaelson, James S.; Bush, Devon M.; Calvillo, Katherina Zabicki; Kopans, Daniel B.; Smith, Barbara L.
<x xml:space="preserve">Abstract</x> BACKGROUND Mortality reduction from mammographic screening is controversial. Individual randomized trials and meta‐analyses demonstrate statistically significant mortality reductions in all age groups invited to screening. In women actually screened, mortality reductions are greater. Individual trials and meta‐analyses show varying rates of mortality reduction, leading to questions about screening's value and whether treatment advances have diminished the importance of early detection. This study hypothesized that breast cancer deaths predominantly occurred in unscreened women. METHODS Invasive breast cancers diagnosed between 1990 and 1999 were followed through 2007. Data included demographics, mammography use, surgical and pathology reports, and recurrence and death dates. Mammograms were categorized as screening or diagnostic based on absence or presence of breast signs or symptoms, and were substantiated by medical records. Breast cancer deaths were defined after documentation of prior distant metastases. Absence of recurrent cancer and lethal other diseases defined death from other causes. RESULTS Invasive breast cancer failure analysis defined 7301 patients between 1990 and 1999, with 1705 documented deaths from breast cancer (n = 609) or other causes (n = 905). Among 609 confirmed breast cancer deaths, 29% were among women who had been screened (19% screen‐detected and 10% interval cancers), whereas 71% were among unscreened women, including > 2 years since last mammogram (6%), or never screened (65%). Overall, 29% of cancer deaths were screened, whereas 71% were unscreened. Median age at diagnosis of fatal cancers was 49 years; in deaths not from breast cancer, median age at diagnosis was 72 years. CONCLUSIONS Most deaths from breast cancer occur in unscreened women. To maximize mortality reduction and life‐years gained, initiation of regular screening before age 50 years should be encouraged. Cancer 2014;120:2839–2846. © 2013 American Cancer Society.